Power electronics and motor control - Shepherd, W. (William), 1928-; Hulley, L. N. (Lance Norman); Liang, D. T. W. (Cambridge : Cambridge University Press, 1995)
This clear and concise advanced textbook is a comprehensive introduction to power electronics. It considers the topics of analogue electronics, electric motor control and adjustable speed electrical drives, both a.c. and d.c. In recent years, great changes have taken place in the types of semiconductor devices used as power switches in engineering applications. In this second edition of a popular text, a further completely new chapter has been added, dealing with the application of PWM techniques in induction motor speed control. The chapters dealing with electronic switching devices and with adjustable speed drives have been entirely rewritten, to ensure the text is completely up-to-date. With numerous worked examples, exercises, and the many diagrams, advanced undergraduates and postgraduates will find this a readable and immensely useful introduction to the subject of power electronics.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Power electronics; Electronic control